The Association of OASL and Type I Interferons in the Pathogenesis and Survival of Intracellular Replicating Bacterial Species - Leisching, Gina; Wiid, Ian; Baker, Bienyameen (Frontiers in Cellular and Infection Microbiology, 2017)
The type I IFN response quickly became associated with its role in the innate immune response to viral infection. The past few years have seen the significance of IFNs expand in breadth to include non-viral pathogens. Previous work has identified that following viral infection, type I IFN signaling induces the production of the 2′‐5′‐oligoadenylate synthetase (OAS) family, which include OAS1, OAS2, OAS3 and OAS‐like (OASL) protein. OASL was identified to be strongly induced following viral infection through engaging the RNA sensor RIG-I and increasing signalling through this pathway to enhance the anti-viral type I IFN response. Surprisingly, infection with viral dsDNA revealed an IFN inhibitory role and therefore pro-viral function of OASL through the inhibition of the cGAS cytosolic DNA sensing mechanism. Intracellular bacteria are able to activate the cytosolic DNA sensing pathway, however the role of OASL during bacterial infection is largely unknown. Vacuolar pathogenic microbes such as mycobacteria induce OASL early post infection, where it functions in a prosurvival fashion by inhibiting autophagic mechanisms and antimicrobial peptide expression. This suggests an underestimated role of OASL in the innate immune response to infection with a variety of pathogens and points to OASL-associated modulation of the type I IFN response. OASL may therefore play a critical role in defining the outcome of infection. We provide a brief update on the recent developments of the OAS family of proteins in response to DNA and RNA virus infections, as well as discuss evidence of Oasl expression in response to a number of cytosolic and vacuolar replicating bacterial pathogens.